Six Sigma Implementation Of Quality Improvement On Chassis Rame Production In Assembly Line (A Case Study At PT Gemala Kempa Daya) - Tannady, Hendy; Gunawan, Gunawan (Teknik dan Ilmu Komputer, 2017)
AbstractÃÂ PT. Gemala Kempa Daya is a member of Astra Otoparts specialized in producing press and automotive assembly, particularly frame chassis. However, many defects are still found in the production lines. The purpose of this research is to improve the quality of the frame chassis assembly so that defective products produced can be reduced, and finally satisfy the customers. In this research, the method of Six Sigma improvement approach, particularly Define-Measure-Analyze-Improve-Control (DMAIC), is employed to improve the quality of the products produced by PT. Gemala Kempa Daya. This study is started at the define phase project. In this step, a bussiness statement, SIPOC diagram and CTQ are made. Making the control map and calculating the sigma value are done in the measure step. The analyze phase describes the problem using Pareto diagrams, Fishbone, and FMEA. Then, improve phase proposes improvements to produce good quality. Finally, the last phase, control phase, controls the improvement. Through the observation conducted, there was a problem during the frame chassis assembly, that improvement and monitoring were required to achieve the target. The calculated sigma value before improvement was 3.622 sigma. After improvements made in March, the sigma value increased to 3.808. One month later, the sigma value increased to 4.012, and in May, the sigma value decreased slightly to 3.903 sigma. It can be concluded that the problem was solved by making the color standard for rivet position, rivet sizes, and making rivet size identity to increase the sigma value.ÃÂ Keywords: quality, six sigma, frame chassis, rivet